Improved livestock feeding yields positive results for Ethiopia's farmers - International Livestock Research Institute (2022)
Improved troughs designed by the Africa RISING project can save 27% of animal feed which would otherwise be wasted. Under the Africa RISING project in Ethiopia, the improved troughs have been designed, tested and evaluated for feeding cattle, sheep and goats. Results from monitoring the use of the improved feed troughs in four sites in Ethiopia showed that they saved 27% of the feed biomass offered to the animals compared to the traditional feed troughs. This film highlights the works of Africa RISING in helping smallholder farmers with this improved technology.